URGENSI STIMULASI KEMAMPUAN MOTORIK KASAR PADA ANAK USIA DINI - BONITA MAHMUD (Didaktika : Jurnal Kependidikan, 2018)
Age 0 - 8 years is the golden age. In this age the child's brain is like a sponge, which is all things that are seen, heard, and felt by children absorbed well by the child. Therefore at this time the child must get the right stimulation in every aspect of his development. One aspect that must be stimulated is gross motoric. This aspect relates to the child's ability to move the large parts of his body, such as the hands and feet. Some activities that can be given to children related to gross motoric skills are jumping, walking, running, and throwing a ball. The disruption of the development of gross motoric aspects in children can affect the development to other aspects. Therefore, the gross motoric aspect must be the one of teachers and parents' concerns as a result the child's development tasks can be achieved according to his age.